SPECTROSCOPIC AND PHYSICOCHEMICAL METHODS FOR STUDYING THE INTERACTION OF METALLOPORPHYRIN WITH DNA - Hidenari Inoue (Universitas Gadjah Mada, 2002)
In recent years studies on the interaction of porphyrin with DNA have received much attention because of the importance in DNA-probing and photodynamic therapy of cancer. A variety of spectroscopic methods, e.g. NMR, ESR, Mössbauer, UV-visible absorption, circular dichroism (CD), magnetic circular dichroism (MCD), IR and Raman spectroscopy, have been employed for studying interactions between porphyrin and DNA. Of these spectroscopic methods, only a few instrumental analytical techniques applicable to an aqueous buffer solution of DNA have been particularly developed to investigate porphyrin-DNA interactions. On the other hand, a number of physicochemical methods, e.g. gel electrophoresis, melting temperature measurements and hydrodynamic methods such as viscosity and sedimentation measurements, have been also used for determining the binding modes of porphyrin to DNA. The present lecture will focus on the application of visible absorption, CD and MCD spectroscopy as well as melting temperature and viscosity measurements to studies of porphyrin-DNA interactions.